Growth performance, flesh fatty acid profile and transcriptome analyses of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) cultured in Deeper-Offshore Aquaculture System - Ziyi Wu; Wenjie Lai; Qinxi Dai; Zhenjiang Zou; Yuyou Lu; Jiachang Xu; Yakang Song; Jingpeng Hou; Haoran Lin; Yong Zhang; Jin Zhang; Danqi Lu (Aquaculture Reports)
Amid the rapid growth of offshore aquaculture in China, a Deeper Offshore Aquaculture System (DOAS) for hybrid Jinhu groupers (Epinephelus fuscoguttatus♀× Epinephelus tukula♂) has been established in Guangdong. This study aims to elucidate the biological and metabolic differences between Jinhu groupers cultured in Recirculating Aquaculture Systems (RAS) and those in DOAS. A three-month growth comparison experiment was conducted to assess the developmental differences of Jinhu groupers. This research reveals significant variations in growth performance and flesh fatty acid composition between fish from these two systems, particularly in the content of eicosapentaenoic acid and nine other fatty acids. Through transcriptome analysis of liver and muscle tissues, 278 and 186 differentially expressed genes were identified, respectively, highlighting notable metabolic shifts. Key pathways affected include lipid metabolism and muscle fiber growth. These insights deepen the understanding of the acclimation mechanisms of Jinhu groupers to diverse aquaculture settings and offer valuable strategies for optimizing deeper offshore aquaculture practices, enhancing the sustainability and efficiency of the industry.